Efektivitas Pembinaan Kemandirian Narapidana di Lembaga Pemasyarakatan Wirogunan Yogyakarta - Muhammad Ali Equatora (Social Welfare Study Program, 2018)
Abstract. Research on the effectiveness in coaching independence prisoners in Wirogunan Yogyakarta has begun and aims to determine the effectiveness in coaching independence inmates start with the implementations aimed at the realization of prisoners who have self-reliance skills. This study used a qualitative descriptive approach, where the primary data found by asking questions of the officials on issues related to assimilation processing job (coaching independence) from both structural field officials. Base on the research, it is known that the effectiveness of coaching independence inmates still not optimal condition apart from several factor, including the human factor other support, human resources, process guidance, available budget and bureaucracy. Effort needs to be done to overcome obstacles in coaching independence inmates were cooperating with the government agencies and institutions in an effort to increase public guidance to prisoners; strong motivation from the persons with the principles of morality and idealist; the effort to improve the walfare agency officials to increase the loyality of officers in carrying out the existence of moral. Researchers sugget the necessity of an understanding of the responsibilities in coaching independent prisoners with all parties, especially the components in the criminal justice system such as police, prosecutors, and court to actively enroll people, and the government and the private sector in efforts to confront obstacles in the face of prison. Abstrak. Penelitian tentang efektifitas pembinaan pada para narapidana yang bebas di Wirogunan Yogyakarta bertujuan guna menentukan efektifitas pembinaan atas mereka yang dimulai dengan berbagai implementasi untuk mewujudkan tahanan yang memiliki keterampilan kemandirian diri. Studi ini menggunakan pendekatan deskriptif kualitatif di mana data primer diperoleh dengan mengajukan pertanyaan pada petugas resmi terkait isu pekerjaan proses asimilasi (melatih tahanan yang bebas) dari petugas yang terbagi secara struktural. Berdasarkan riset ini, diketahui bahwa efektifitas pembinaan narapidana jauh dari kondisi optimal terkait beberapa faktor yang meliputi faktor kemanusiaan, seperti dukungan, sumber daya manusia, pembinaan, ketersediaan anggaran, dan birokrasi. Upaya yang diperlukan untuk mengatasi tantangan pembinaan narapidana yang bebas adalah bekerjasama dengan agen-agen pemerintah dan berbagai lembaga guna meningkatkan peningkatkan pembinaan narapidana, motivasi yang kuat dari orang-orang beserta prinsip-prinsip moralitas dan idealisme, upaya meningkatkan kesejahteraan oleh petugas guna meningkatkan loyalitas dalam mengemban eksistensi moral. Peneliti menyarankan perlunya pemahaman tanggung jawab dalam membina narapidana bebas dengan seluruh bagian-bagiannya khususnya komponen-komponen di dalam sistem keadilan hukum seperti polisi, jaksa, dan pengadilan agar secara aktif mendaftarkan masyarakat, pemerintah dan sektor privat dalam upaya mengatasi tantangan menghadapi narapidana.